EOCENE LARGER FORAMINIFERAL BIOSTRATIGRAPHY IN THE SOUTHERNMOST DAUPHINOIS DOMAIN (MARITIME ALPS, FRANCE-ITALY BORDER) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
The Trucco Formation and the Nummulitic Limestone (Dauphinois Domain, Maritime Alps) are characterized by abundant larger foraminifera, specifically nummulitids, orthophragminids and encrusting foraminifera. In the Maritime Alps, previous studies suggest a late Lutetian age for the Trucco Formation and a late Lutetian-Priabonian age for the Nummulitic Limestone.Biostratigraphic analysis of the nummulitids, in 11 stratigraphic sections, allowed us to distinguish 3 biozones:MALF1 Zone: defined by the presence of Nummulites brongniarti d’Archiac & Haime, N. puschi d’Archiac, N. perforatus de Montfort, N. striatus (Bruguière), N. cf. dufrenoyi d’Archiac & Haime, N. variolarius/incrassatus and Operculina schwageri Silvestri.MALF2 Zone: defined by the presence of Nummulites perforatus de Montfort, N. striatus (Bruguière), N. cf. dufrenoyi d’Archiac & Haime, N. variolarius/incrassatus and Operculina schwageri Silvestri.MALF 3 Zone: defined by the presence of gr. Nummulites variolarius/incrassatus, N. striatus (Bruguière) and Operculina schwageri Silvestri.According to current larger foraminiferal biozonal schemes, the age of these local biozones corresponds to the Bartonian p.p.Moreover, the comparison with biostratigraphic schemes established for the Dauphinois Domain and for the Tethyan area evidences that several typical nummulitid species of the late Bartonian are lacking in the southern Dauphinois Domain, probably due to a paleogeographic control.
Keywords: Biostratigraphy; Nummulites; Eocene; Dauphinois Domain; Maritime Alps